Mitigation Strategies of Heating Pipe Leakage a Case Study on Crude Oil Tanker MT. Griya Cirebon - Nevlin Airlangga Rustanto, Audrey; Geleuk Sengadji , Karolus; Hermina Sari, Ria; Trinata Pramudhita, Manungku (Politeknik Ilmu Pelayaran Semarang, 2025)
Abstract: Heating pipes are one of the crucial factors of the cargo operation on crude oil vessels. The heating pipes heat the cargo, allowing it to be pumped and transported easily. The heating pipe plays a crucial role, considering the nature of crude oil, which easily thickens. The heating pipe is essential to maintain the temperature of the crude oil cargo at a normal level, allowing loading and unloading activities to run optimally. This research aims to identify the factors that cause heating pipe leakage, analyze its impact, and develop mitigation strategies. The method used in this research is a qualitative method. Triangulation data of observation, interviews and documentation study were used in this research. The collected data were then analyzed qualitatively to answer the problem. This study identifies several factors that contribute to heating pipe leaks, including corrosion from exposure to seawater, lack of routine maintenance, and the aging of the pipes. The impact caused a decrease in oil temperature, which disrupts the loading and unloading process and leads to crews working overtime. To address these issues, it is recommended to monitor the vapor pressure of the heating pipes, conduct regular maintenance, and replace old pipes with new stainless-steel material.